Effect of uses of Probiotic prepared from Lactobacillus acidophilus Bacteria as immunostimulator in lambs vaccinated with Brucella melitensis Rev-1 vaccine: Yousif. A.A. and Al umary. A. J. A. - A., Yousif A. (The Iraqi Journal of Veterinary Medicine, 2009)
This study was conducted to investigate the effect of probiotic prepared from Lactobacillus acidophilus & usedas immunostimulator to improve the humeral &cellular immune response in lambs vaccinated with the Rev-1 vaccine.Lactobacillus isolated from intestinal contents of sheep after culturing on specific media &study the morphological &biochemical characteristic Lactobacillus acidophilus was selected as probiotic after definitive diagnosis and dependingon their higher adherence ability to epithelial cells of the intestine and have high tolerance to low pH and bile salts .thensensitivity test of the strain against antibiotics was done The experimental study included 15 lambs (age 5-8 months)were equally divided into three groups and treated as following.* First group was vaccinated with Rev -1 vaccine (1ml contain 2×109CFU- s/c as single dose ) and ioculated orally withprepared probiotic (2 ×109 CFU /lamb ) at one week before vaccination and continued daily to end of experiment(14weeks).*Second group was vaccinated only with Rev -1 vaccine at same way in first group. *Third group was inoculated with 1ml PBS S\c as control group. Clinical and immunological tests were conducted to all lambs at 0 times & after 2, 6, 10, 14weeks. The results of clinical tests revealed that there is increase in body temperature, respiratory &pulse rates ofvaccinated animals only but the second group show the highest parameters. The vaccinated lambs shows humeralimmune response by giving a positive results to rose Bengal test & by using Passive haemagglutination test, the firstgroup revealed high significant antibody titer (716.80±125.413) than the second group and third group (p<0.05 ) . andthe results of cellular immune response, as detected by delayed type hypersensitivity test which give a positive results invaccinated groups but the first group was significantly higher (p<0.05 )at than rates in redness area and thicknesscompared with the second group E. rosette test showed significant increase at(p<0.05 ) of activated lymphocyte infirst group ( 51.976±4.619 )compared with second (41.22±3.6865). Serum total protein concentration was increased infirst group (9.7358±0.2615) compared with other groups.